Pembelajaran Al-Qur’an Dengan Metode Jari Dalam Upaya Meningkatkan Baca Tulis Al-Qur’an Di TPA An-Nida Krebet Gumukmas Jember - Siti Nursyamsiyah; Cahya Tribagus Hidayat (Jurnal Pengabdian Masyarakat IPTEKS, 2020)
AL-Quran Al-Karim is the last miracle revealed to the Prophet Muhammad, and as a way of life for Muslims. As inheritors of the earth, has the obligation for all Muslims to learn starting from learning to read letters hijaiyah were first introduced in early childhood. In addition to the ability to read the Qur'an, an increase in the ability to write the Koran should be noted, due to the fact this is a weakness aspects of writing a large part of children and even adults.Jari-Qur`an teaching methods encourage children chanting in an atmosphere of joy and love, children and educators are encouraged to set an example and want to take the example of the good nature of anyone, and to make the example of the Prophet became a major base in the moral formation of children , The process of teaching is done in ways that favored child, namely in the form of fairy tales, games, prizes, props, songs, and exercises. Jari-Qur`an excess compared with the methods of the Qur'an to read and write more lies in the placement and grouping of the letters hijaiyah into geometric shapes making it easier for children to remember reading and writing, how to use a very easy and fun with a variety of props, stories, songs, and games, using different colors so as to stimulate the creativity of children,